A new silicon detector telescope for measuring the linear energy transfer distribution over the range from 0.2 to 400 keV/micrometer in space - Doke, T (Japanese journal of applied physics, 1996)
A new telescope consisting of three two-dimensional position-sensitive silicon detectors which can measure the linear energy transfer (LET) distribution over the range from 0.2 to 400keV/micrometers has been developed as a real-time radiation monitor in manned spacecraft. First, the principle of LET measurement and its design method are described. Second, suitable electronic parameters for the LET measurement are experimentally determined. Finally the telescope performance is investigated by using, relativistic heavy ions. The first in-flight test of this type of telescope on the US Space Shuttle (STS-84) is scheduled for May, 1997